2022
DOI: 10.1111/1467-9566.13436
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation: Governing actual uncertainty in the coronavirus pandemic

Abstract: The coronavirus pandemic has revived scholarly engagement with the concept of biopolitics, with interpretations diagnosing either the widespread adoption of a classic biopolitical regime or the full‐blown emergence of totalitarian repression (or both of these simultaneously). Relying on a close analysis of different interventions taken by Israeli authorities in response to the pandemic, this article argues that, rather than classic biopolitical strategies, such governmental interventions are better understood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…COVID-19 resulted in many participants re-living the hardships of the HIV/AIDS pandemic, while also leveraging their experience to navigate COVID-19. While previous research has demonstrated how uncertainty produces distress (e.g., Author et al, 2020 ; Nettleton, Watt, O’Malley, & Duffey, 2005 ; Timmermans & Buchbinder, 2013 ) and connected the COVID-19 pandemic to such uncertainty (e.g., Lalot, Abrams, & Travaglino, 2021 ; Rabi, Samimian-Darash, & Hilberg, 2022 ), study participants were instead distressed by the familiarity of the pandemic and how it resembled their previous experiences with HIV/AIDS. This finding highlights the importance of psychosocial supports not only during but after a pandemic.…”
Section: Discussionmentioning
confidence: 72%
“…COVID-19 resulted in many participants re-living the hardships of the HIV/AIDS pandemic, while also leveraging their experience to navigate COVID-19. While previous research has demonstrated how uncertainty produces distress (e.g., Author et al, 2020 ; Nettleton, Watt, O’Malley, & Duffey, 2005 ; Timmermans & Buchbinder, 2013 ) and connected the COVID-19 pandemic to such uncertainty (e.g., Lalot, Abrams, & Travaglino, 2021 ; Rabi, Samimian-Darash, & Hilberg, 2022 ), study participants were instead distressed by the familiarity of the pandemic and how it resembled their previous experiences with HIV/AIDS. This finding highlights the importance of psychosocial supports not only during but after a pandemic.…”
Section: Discussionmentioning
confidence: 72%
“…In contrast, Rabi et al. (2021) compares Foucault, Agamben and Latour, choosing to emphasise Latour’s (2020) interest in ‘biopolitics’ as a form of statistics‐based management as following Foucault’s interest in population health (against Clover, 2020).
It is the state of the nineteenth century and so‐ called biopower … the state of what is rightly called statistics: population management on a territorial grid seen from above and led by the power of experts.
…”
Section: Design and Materialitymentioning
confidence: 99%
“…Meanwhile Marks (2021) uses Actor-network theory (Latour, 1987(Latour, , 2005 and Latour read in part through Duff (2016) and partly through Serres and Latour (1995) to help account for emotional distress and its amelioration through bicycle repair. In contrast, Rabi et al (2021) compares Foucault, Agamben and Latour, choosing to emphasise Latour's (2020) interest in 'biopolitics' as a form of statistics-based management as following Foucault's interest in population health (against Clover, 2020).…”
Section: Design and Materialitymentioning
confidence: 99%
“…it mean[s] to live “in” a state of emergency?’ (Anderson, 2017: 464). Assessing emergency experience becomes a way to understand the new pandemic ‘milieu of actual uncertainty ’ (Rabi et al, 2022: 587, emphasis in original), to ‘anticipate unwanted scenarios and initiate mitigating measures’ (WHO, 2020f: 10), and to gauge the emergence of the pandemic itself.…”
Section: Problematising Pandemic Fatiguementioning
confidence: 99%
“… 2. The article thus opts for a mode of theorising that follows ‘how specific biopolitical technologies are emerging in response to distinct problems’ (Rabi et al, 2022: 578) to avoid the pitfalls involved in an epochal reading of the Covid-19 pandemic as a grim biopolitical horizon ‘straight out of a Michel Foucault lecture’ (Latour, 2021: S26; for a reading more blatantly bordering on conspiracy thinking see Agamben, 2021). It thus approaches pandemic governance as potentially ‘legitimate but [.…”
mentioning
confidence: 99%